Iot Based Industrial Pollution Monitoring System - Keerthi J; Sneha; Pavithra R; Shashikala (International Journal of Pollution: Prevention & Control, 2024)
This paper introduces a robust IoT-based industrial pollution monitoring system aimed at addressing the critical need for effective environmental management in industrial settings. By leveraging sensor networks and real-time data analytics, the system provides continuous monitoring of various pollutants emitted from industrial activities. The integration of IoT devices streamlines data collection, transmission, and analysis, offering timely insights for proactive decision-making. This system not only facilitates compliance with environmental regulations but also helps mitigate adverse impacts on surrounding ecosystems, thereby promoting sustainable industrial practices. The proposed solution underscores the importance of utilizing IoT capabilities to foster environmental sustainability and enhance the well-being of communities affected by industrial operations. Through continuous monitoring and immediate data processing, the system ensures that industrial pollution is kept within permissible levels, reducing the risk of environmental harm. Additionally, the real-time feedback loop allows industries to promptly address pollution incidents, preventing long-term ecological damage. Overall, this innovative approach demonstrates how advanced technology can be harnessed to achieve a balance between industrial development and environmental preservation, ensuring a healthier and more sustainable future for all.
Keywords: Environmental sustainability; IOT; Industrial pollution; Real-time Data; monitoring system; sensor networks